Evolution and determinants of public investment in Europe - Timo Välilä; Aaron Mehrotra (European Investment Bank (EIB), 2005)
We examine the evolution of public investment and public capital stocks in Europe during the past three decades. Against this background, we employ an array of econometric techniques to assess the macroeconomic determinants of public investment, with a special focus on its long-term trend. We find that public investment has been determined by national income, the stance of budgetary policies, and fiscal sustainability considerations. Neither the cost of financing nor the fiscal rules embodied in EMU have had a systemic impact on public investment. The significant downtrend that characterises the evolution of public investment, measured in relation to GDP, in non-cohesion countries is chiefly determined by drawn-out episodes of fiscal consolidation, unrelated to EMU.
Keywords: E62; H54; C23; 330